COMPARISON OF THE EFFECTS OF REMINISCENCE THERAPY ALONE AND IN COMBINATION WITH PSYCHOEDUCATION THERAPY ON DEPRESSION LEVEL OF ELDERLY IN INDONESIA: A QUASI-EXPERIMENTAL STUDY - Sutinah Sutinah (Belitung Nursing Journal, 2020)
Background: Depression can occur in elderly, but it is not a part of normal aging. Untreated depression increases rates of completed suicide and mortality. Therefore, an effort to reduce depression level is needed. Reminiscence and psychoeducation therapy are assumed to be effective in reducing the level of depression in elderly. Objective: To compare the effects of reminiscence therapy alone and in combination with psychoeducation therapy on depression level in elderly. Methods: This study employed a quasi-experiment with comparison group design. Seventy-two respondents were selected in this study using a simple random sampling, which 36 were assigned in each group. Data were collected in 2018 using Geriatric Depression Scale (GDS). Dependent and Independent t-test were used for data analyses. Results: The reminiscence therapy alone or in combination with the psychoeducation therapy were effective in reducing depression level in elderly (p<.05). The combination of reminiscence and psychoeducation therapy was much more effective than reminiscence therapy alone (p<.05). Conclusion: These findings serve as an input for the Government of Indonesia to provide the combination of the reminiscence and psychoeducation therapy in the elderly program. This study provides a new knowledge for geriatric nurses to provide new interventions specifically to reduce depression level among elderly.